Phatics and pragmatics of the headline in sports discourse in forming a provocative narrative - Zahra, O. V. (Гуманитарные и юридические исследования, 2024)
Introduction. Nowadays a constitutively determined description of sporting events becomes a powerful tool for the formation of national ideology and culture. The study of headline complexes in sports publications provides an insight into the mechanisms of manifestation of phatic and manipulative functions, which are currently dominant in the language of the media. Materials and Methods. The article, based on a contaminated classification of the discursive significance of sports news and discourse-modus analysis, taking into account the focus of the addressee, analyzes various types of headlines as basic codes for interpreting the main text of messages, their main functions and the functional pragmatics of influencing a hypothetical recipient. Analysis. Particular attention is paid to the comparison of specifiers of phatic and informational orientation as the most representative mechanisms of bidirectional vectors operating within the framework of increasing the relevance of the described event and the socio-cultural and ideological phenomena associated with it. The author argues that the use of manipulative and phaticoexplicatory techniques in headlines realizes the maximum perlocutionary effect, if a balance between episodic sensationalism and operational information content is maintained. Taking into account the complex of axiological dominants in the compressed space of the title is recognized as a basic condition for attracting the attention of a wide range of readers; and the use of units that mark the exclusivity and episodic determinism of the described news item is the most effective methods for realizing the maximum manipulative effect. Results. The headline complex is the most compressed regulatoryphatic model of the entire text of the description, which includes settings for interpreting the entire description and specifies the axiological vectors for evaluating the news feed. At the same time, the strong position of the text, which the title represents, activates the attention of the readership through provocative narrativization, affecting associations with other socially significant areas.